STAKEHOLDER'S PERCEPTION OF TRANSPARENCY IN VILLAGE FUND MANAGEMENT IN TOTO SELATAN VILLAGE, KABILA DISTRICT, BONE BOLANGO REGENCY - Katili, Sartin; Rizal; Hamzah, Aryati (LP2M Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine stakeholder perceptions of the Transparency ofVillage Fund Management in South Toto Village, Kabila District, Bone BolangoRegency, with reference to the Minister of Home Affairs Regulation No. 20 of 2018concerning Village Financial Management.This research method uses descriptive research with a qualitative approach. Datacollection techniques used in this study was through observation, in-depth interviewsand documentation.The results of this study indicate that stakeholder access in the budgetaccountability report has been carried out in the form of a Transparency Board /Billboard, so that all activities and their budgets can be seen by stakeholders. Theweakness is that if there is a change in activities and budgets, then stakeholders donot have access to these changes. Independent audit involvement in budgettransparency has been carried out. The audit was carried out by the RegencyInspectorate regarding finances and accountability reports for all activities that hadbeen carried out. The weakness is that most stakeholders do not know the results ofthe examination or audit. Stakeholder involvement in budget decision making hasbeen carried out, every planning stage always involves the BPD, LPM and thecommunity. The weakness is that community involvement is only in the form ofproviding ideas and proposals related to the needs in each hamlet, but the stages ofdetermining them are no longer involved.